'You're my kwertengerl': transforming models of care for central Australian aboriginal museum collections. (4th May 2019) - Gibson, Jason
ABSTRACT: This article provides ethnographic insights into the ways in which museums are being engaged with and positioned by some Aboriginal people in Central Australia. At the centre of this analysis is the stated suggestion of some Anmatyerr and Arrernte men that museums be incorporated into their social-cultural frameworks and thus brought into their systems of relating. Drawing upon endeavours to return and repatriate key central Australian collections, I reveal the complex relationship between these communities, collecting institutions and their staff. This research also highlights the agency of Anmatyerr and Arrernte people in their dealings with the ethnographer and collector, T.G.H. Strehlow, and shows how they now wish to encompass museums and other collecting institutions in a relationship founded upon complementary roles and responsibilities. Their interest in positioning the museum as a kwertengerl, meaning a 'manager' or 'worker' that upholds the interests of traditional owners, presents both a challenge and an opportunity for the relevant institutions.